A promising nanoporous AlxGa(1-x)N nanosheet based on octagraphene - Fabris, Guilherme S.L.; Paskocimas, Carlos A.; Sambrano, Julio R. [UNESP]; Paupitz, Ricardo [UNESP] (Elsevier, 2021)
A new class of 2D inorganic materials named octa-AlxGa(1-x)N (x=0,0.25,0.5,0.75and1) with the octa-graphene architecture is theoretically investigated by Density Functional Theory simulations. It was found that the energy band gap increased with the introduction of Al atoms. The calculated Young modulus is within the range (46.02 N/m ⩽Y2D⩽53.66 N/m) and Poisson's ratio within (0.733⩽ν⩽0.783), while frequency calculations reveal that these structures are dynamically stable. Energetic barriers for Li, Na and K diffusion were also studied and were found values lower than those calculated for octa-graphene in a previous work.
Keywords: 2D-Materials; Density Functional Theory; Electronic Structure; GaN; Hackelite; Octa-graphene; Raman